PERAN MAHASISWA SEKOLAH TINGGI TEOLOGI ARASTAMAR BENGKULU DALAM MEMUTUS RANTAI PENYEBARAN PANDEMIK CORONA VIRUSES DISEASE 19 - Made Nopen Supriadi; Gusman Novir Giawa; Iman Kristina Halawa (Sekolah Tinggi Teologi Injili Arastamar (SETIA) Jakarta, 2021)
The Covid-19 pandemic has an impact on many aspects of human life, this is experienced by theological schools in Indonesia, many high schools in Indonesia have difficulty adapting specifically to carry out teaching and learning activities during the Covid-19 pandemic. Theological colleges in Indonesia have also experienced the impact of becoming clusters or becoming the center of the spread of Covid-19. Bengkulu Arastamar Theological College (STTAB) is one of the theological colleges that has experienced the impact of the Covid-19 pandemic. STTAB has participated in preventing the spread of Covid-19 by involving students to play an active role in implementing health protocols. The role of STTAB students in breaking the chain of the spread of Covid-19 by implementing health protocols. This paper applies a descriptive research method to explain the background and role of the theological school. The results of this study are to contribute to other theological colleges in Indonesia to stop the spread of Covid-19 through the role of STTAB students.